2018
DOI: 10.15208/beh.2018.60
|View full text |Cite
|
Sign up to set email alerts
|

Can disclosure practices and stakeholder management influence zakat payers’ trust? A Malaysian evidence

Abstract: This study examines whether disclosure practices and stakeholder management play an important role in influencing the zakat payers' trust in the zakat institutions in Malaysia. A regression analysis was performed to examine the relationship between disclosure practices and stakeholder management of the zakat institutions on zakat payers' trust. Using questionnaire survey on 184 zakat payers, this study shows that the disclosure practices do influence the zakat payers' trust in the zakat institutions. However, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
12

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 22 publications
1
12
0
12
Order By: Relevance
“…Official website should ensure enough information available such as the process of zakat application, programs conducted, zakat distribution summary, method of zakat payment and other relevant data. However, there are some challenges in collecting relevant zakat information especially on the reporting aspects (Samargandi et al, 2018;Sapingi, Nelson & Obid, 2018;Sulaiman, Che Cob, & Ali 2015). A study found that only 7% of the respondent gathered zakat information through official zakat website while other channel used are through relative friends, newspaper, memo and radio (Raja Ahmad, Amiruddin Othman, & Salleh, 2015).…”
Section: Transparent Information (Zakat Institution Website)mentioning
confidence: 99%
“…Official website should ensure enough information available such as the process of zakat application, programs conducted, zakat distribution summary, method of zakat payment and other relevant data. However, there are some challenges in collecting relevant zakat information especially on the reporting aspects (Samargandi et al, 2018;Sapingi, Nelson & Obid, 2018;Sulaiman, Che Cob, & Ali 2015). A study found that only 7% of the respondent gathered zakat information through official zakat website while other channel used are through relative friends, newspaper, memo and radio (Raja Ahmad, Amiruddin Othman, & Salleh, 2015).…”
Section: Transparent Information (Zakat Institution Website)mentioning
confidence: 99%
“…The research conducted by Mital et al (2010) andDuffy et al (2011) concluded that the level of trust in the organization depends on the quality and disclosure of financial information. Likewise, Mustafa et al (2013) and Samargandi et al (2018) at zakat institutions concluded that to increase muzakki's trust, zakat institutions must disclose financial information and other information to ensure the institution is valid and legitimate.…”
Section: Financial Reporting Qualitymentioning
confidence: 99%
“…Mustafa et al (2013) stated that zakat payers need broad-based information relating to financial matters to prove that the institution is valid and legitimate. According to Samargandi et al (2018), zakat institutions should focus on transparency in disclosing practices to increase the trust of zakat payers in them. One of the most important information for muzakki is financial information presented in the form of financial reporting as a form of transparency and accountability in the management of zakat funds by ZMO.…”
Section: Introductionmentioning
confidence: 99%
“…7. The disclosure is expected to increase the trust of Muzaki to donate in LAZ (Samargandi et al, 2018). Fundraising (F1) will be escalated, hence, maximisation of fund distribution (F3) to promote the welfare and prevent harmfulness as well as poverty alleviation (Ahmed, 2011;Zakaria et al, 2014).…”
Section: Relationship Of Perspectives and Strategic Objectivesmentioning
confidence: 99%